2023
DOI: 10.1002/adma.202306290
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Ambipolar Heterojunctions: Materials, Devices, and Circuits

You Meng,
Weijun Wang,
Wei Wang
et al.

Abstract: Anti‐ambipolar heterojunctions are vital in constructing high‐frequency oscillators, fast switches, and multivalued logic (MVL) devices, which hold promising potential for next‐generation integrated circuit chips and telecommunication technologies. Thanks to strategic material design and device integration, anti‐ambipolar heterojunctions have demonstrated unparalleled device and circuit performance that surpasses other semiconducting material systems. This review aims to provide a comprehensive summary of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 258 publications
0
2
0
Order By: Relevance
“…Moreover, the 2D/3D integration structure offers additional advantages, including high absorption coefficient and high integration density 22,23 . These features facilitate the design and implementation of complex logic functionalities through multidevice cooperation 24 . Consequently, this method offers significant promise as a candidate for realizing all-optical logical gates and potentially replacing existing technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the 2D/3D integration structure offers additional advantages, including high absorption coefficient and high integration density 22,23 . These features facilitate the design and implementation of complex logic functionalities through multidevice cooperation 24 . Consequently, this method offers significant promise as a candidate for realizing all-optical logical gates and potentially replacing existing technologies.…”
Section: Introductionmentioning
confidence: 99%
“…[33,34] Such phenomena are driven by the transition between n-type and p-type dominated operation regime, which is characterized by the threshold voltages in both n-and p-channels, as well as the band alignment configurations. [19,35,36] Gaussian functions are extensively used in constructing advanced computing algorithms, such as building statistical distributions in language processing algorithms, accounting for Bayesian uncertainties, and tuning/filtering functions in computer vision algorithms. [37][38][39] Therefore, Gaussiantype transistors with such unique electrical transport characteristics are identified as promising candidates in hardwarelevel implementations of artificial learning paradigms, such as spike-generate signals for spiking neuron networks and Gaussian synapses for probabilistic neural networks, [40,41] envisioning their significant potential in advanced computing architectures.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Typically, AATs are based on asymmetric device structures in which n-type and p-type semiconductors are located at both ends, creating a p-n heterojunction at the middle overlapping part. 1,2 Particularly, the turn-on voltage of a p-type semiconductor needs to be larger than that of the n-type counterpart. 1−3 It is generally assumed that the spike-shaped transient current of AATs occurs when both p-and n-channels in series are simultaneously in the on-state.…”
mentioning
confidence: 99%
“…Distinctly different from unipolar field-effect transistors and conventional ambipolar devices, anti-ambipolar transistors (AATs) are devices that exhibit a convex-shaped transfer characteristic, where the channel electrical conductance peaks at a specific gate bias. , Typically, AATs are based on asymmetric device structures in which n-type and p-type semiconductors are located at both ends, creating a p-n heterojunction at the middle overlapping part. , Particularly, the turn-on voltage of a p-type semiconductor needs to be larger than that of the n-type counterpart. It is generally assumed that the spike-shaped transient current of AATs occurs when both p- and n-channels in series are simultaneously in the on-state. Hence, the design of AATs requires carefully matched turn-on voltages for the p/n-type semiconductors, precisely controlled carrier density, and elaborate energy band alignment. , Currently, researchers have developed many outstanding AATs, including MoS 2 /MoTe 2 , , 1D GaAsSb/2D MoS 2 , InSe/WSe 2 , MoTe 2 /SnS 2 , and more. In fact, this anti-ambipolar characteristic has crucial applications in logic circuits, optoelectronics, and quantum superposition state processing. ,, For instance, by utilizing the flipping of transconductance, these devices can be applied to construct frequency doublers, binary phase-shift keying, and ternary inverters. Additionally, recent studies have found that light can act as a switch to realize the device conversion between binary and multivalued logic (MVL), providing a new paradigm for information encryption . Additionally to the aforementioned features, adjusting the different energy band alignments within the heterojunction through gate control enables the manipulation of the separation and transport of photoinduced carriers, enabling optimization of photocurrent amplitude. , This characteristic can be utilized for the effective capture of optical signals. , …”
mentioning
confidence: 99%
See 1 more Smart Citation